Sperm morphometric in males of the paper wasp Polistes simillimus - De Souza, Andre Rodrigues; Folly, Camila; Dias, Glenda; Santos, Eduardo Fernando dos [UNESP]; Lino-Neto, Jose (Alma Mater Studiorum, Univ Bologna, 2018)
Intraspecific variation in sperm morphometric is widespread across animal taxa and it might be related to different aspects of sexual selection. Within social insects, it has only been documented for some bee and ant species. Here we provided a detailed description of the variation in sperm morphometric in the paper wasp Polistes simillimus Zikan (Hymenoptera Vespidae). Light microscopy, digital photography and digital analyses were used to measure sperm (total length, head and flagellum length). Considering a single population from which we sampled four colonies, seven males of each colony and 30 sperm cells of each male (total 840 cells), the overall dimensions of P. simillimus spermatozoon is: total length 107 +/- 7 (80-129) mu m, coefficient of variation, CV = 8%; flagellum length 91 +/- 7 (62-114) mu m, CV = 7%; head length 16 +/- 2 (9-30) mu m, CV = 9%. We found that variation in the sperm constituent parts (head and flagellum) contribute to explaining the variation in total sperm length. However, the size of these parts varies independently. Besides, sperm total length and flagellum length differed between males, but not between nestmates and between colonies, while variation in sperm head was similar across all these levels of analyses. Finally, sperm morphometric is not associated with male body size. We discussed implications of our results for the study of sperm morphometric in insects, sampling procedures for estimating species-typical sperm size in social insects and the possibility of variation in male sperm quality in social wasps.
Keywords: paper wasps; sampling procedure; sperm size evolution; sperm quality; variation in sperm length